2007
DOI: 10.1111/j.1365-3180.2007.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing after‐ripening response and germination requirements of Conyza canadensis and C. bonariensis (Asteraceae) through logistic functions

Abstract: SummaryGermination requirements and after-ripening effects during one year of dry storage at 15/5 and 25/15°C (day/night) were compared for Conyza bonariensis and C. canadensis (Asteraceae). A logistic function was fitted to the results from tests over time in various incubation conditions, using three populations of each species as replicates. Time required for response to dry storage was measured by using a new method; the third derivative of the logistic function. Therefore, a point when major germination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 34 publications
(54 reference statements)
1
32
0
5
Order By: Relevance
“…Values were reduced in relation to the initial germination, remaining constant from June (second period) to November (seventh period), and from December (eighth period) on, there were increases at each collection. A study revealed the occurrence of a primary dormancy as a physiological mechanism in horseweed seeds (Karlsson and Milberg, 2007), although there are studies that indicate the absence of dormancy in seeds from this species (Lazaroto et al, 2008;Constantin et al, 2013). In this study, it was possible to observe initial germination and reduction after the first collection period; this can be considered as a secondary dormancy.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Values were reduced in relation to the initial germination, remaining constant from June (second period) to November (seventh period), and from December (eighth period) on, there were increases at each collection. A study revealed the occurrence of a primary dormancy as a physiological mechanism in horseweed seeds (Karlsson and Milberg, 2007), although there are studies that indicate the absence of dormancy in seeds from this species (Lazaroto et al, 2008;Constantin et al, 2013). In this study, it was possible to observe initial germination and reduction after the first collection period; this can be considered as a secondary dormancy.…”
Section: Resultsmentioning
confidence: 63%
“…In this study, it was possible to observe initial germination and reduction after the first collection period; this can be considered as a secondary dormancy. In case of species such as horseweed, which show primary dormancy as physiological mechanism (Karlsson and Milberg, 2007), with unfavorable environmental conditions for germination, they have the capacity to develop a secondary dormancy (Baskin and Baskin, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has been recently shown that alternative functions that allow for a rightskewed distribution of Ψ b (g), such as the log-logistic, inverse normal or lognormal distributions, depending on the species, can provide a more accurate fit to germination data (Mesgaran et al, 2013). Karlsson and Milberg (2007) found a good fit for C. bonariensis germination data with the logistic function, the possibility remains that alternative functions might give better fit. However, various researchers have utilized normally-distributed hydrotime model to estimate hydrotime constant, base water potential and standard deviation for different plant seed species (Windauer et al, 2006;Mesgaran et al, 2013;Huarte, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Rapeseed (Brassica napus), which exhibits primary dormancy (KARLSSON & MILBERG, 2007), reveals that the lack of environmental factors that promote the germination can induce secondary dormancy (MOMOH et al, 2002). Thus, it is believed that the horseweed seeds buried at up to 0.5cm depth was sufficient to modify quality of the light and the seeds did not receive the necessary stimulus to germinate; although, study indicates that this depth is sufficient for horseweed seed to germinate (VIDAL et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…There is a controversy related to seed dormancy, some researchers reported that the horseweed seed has no dormancy (CONSTANTIN et al, 2013); however, another research informed 80% of physiological dormancy (KARLSSON & MILBERG, 2007). Also, it was verified for this species that the seeds exhibited quiescence under conditions of insufficient light or temperature, and the germination process restarts once the limiting factor is controlled (YAMASHITA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%